2020
DOI: 10.3390/nu12041201
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adipokines Profile in Prepubertal Children with a History of Prematurity or Extrauterine Growth Restriction

Abstract: Adipose tissue programming could be developed in very preterm infants with extrauterine growth restriction (EUGR), with an adverse impact on long-term metabolic status, as was studied in intrauterine growth restriction patterns. The aim of this cohort study was to evaluate the difference in levels of plasma adipokines in children with a history of EUGR. A total of 211 school age prepubertal children were examined: 38 with a history of prematurity and EUGR (EUGR), 50 with a history of prematurity with adequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 68 publications
(96 reference statements)
0
14
0
Order By: Relevance
“…Studies have found that preterm infants with EUGR are at increased risk of developing respiratory disease after their discharge from the hospital. They are also prone to developing physical dysplasia in the short term and may encounter complications such as adolescent hypertension, metabolic and endocrine abnormalities, and serious neurological development problems in the long term, which may affect quality of life (2)(3)(4)(5). Therefore, EUGR is still a serious problem in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that preterm infants with EUGR are at increased risk of developing respiratory disease after their discharge from the hospital. They are also prone to developing physical dysplasia in the short term and may encounter complications such as adolescent hypertension, metabolic and endocrine abnormalities, and serious neurological development problems in the long term, which may affect quality of life (2)(3)(4)(5). Therefore, EUGR is still a serious problem in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…To help to elucidate this question, we conducted a prospective study in preterm children without FGR, with and without EUGR, which were evaluated later at prepubertal age, from 6 to 13 years old. Some of the results of this study have recently been published, showing an increased risk of cardiometabolic alterations, changes in plasma adipokines' profile and higher low-grade inflammation in preterm children with EUGR compared with those growing properly and term children (19,20). Early programming of the adipose tissue has been suggested in EUGR children.…”
Section: Introductionmentioning
confidence: 76%
“…The sample involved 211 Caucasian children born between 1996 and 2008, recruited at school age with prepubertal status (Tanner 1) and delivered in the same neonatal unit in a tertiary hospital. Children were classified into one of three groups, as reported elsewhere (19,20). Briefly, the first group, identified as the EUGR group, included prepubertal children with the following criteria: a history of prematurity: ≤32 weeks gestational age (GA); a weight above P10 for GA at birth and without the diagnosis of FGR following the international consensus of the Ultrasound Obstetrics and Gynaecology (22); the development of postnatal growth restriction or "a true EUGR, " according to the definitions proposed in the literature (weight <P3 at 36 weekspostmenstrual age and discharge from the neonatal unit) (18).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is already in early infancy that various functional system disorders (gastrointestinal, cardiovascular, neural, etc.) and type 2 diabetes are diagnosed in such children [ 17 , 18 , 19 , 20 ]. Therefore, researchers are focused on studying the causes and pathogenic mechanisms of endocrine pathology development in children in early ontogenesis.…”
Section: Introductionmentioning
confidence: 99%